Identification of Mechanical Peropeties of Composite Plates using a Non-Destructive fast Convergence Method (London Journal of Engineering Research, 2023)
The main purpose of this study is to extract the material properties of a composite plate. Hence, a non-destructive fast convergence method has been proposed to achieve this aim. In this regard, the free vibration test data is first measured using modal analysis. Using the differential quadrature method (DQM) based on first-order deformation theory (FSDT), a standard eigenvalue problem is then provided to calculate natural frequencies. The genetic algorithm is then coupled with the differential quadrature method to find the material properties of a composite plate. Finally, the obtained results are compared and validated with available results in the literature, which show high accuracy and a fast convergence rate.
Keywords: composite plate; differential quadrature method; genetic algorithm; non-destructive method; modal analysis.